DANGER IN THE INTENSIVE CARE UNIT: DAMPS IN CRITICALLY ILL PATIENTS. Issue 2 (February 2016) - Timmermans, Kim; Kox, Matthijs; Scheffer, Gert Jan; Pickkers, Peter
Abstract : ABSTRACT: Danger-associated molecular patterns (DAMPs) that are released by injured, threatened, or dead cells, or that originate from the extracellular matrix, influence the immune system. This is of great relevance in critically ill patients, in whom trauma or surgery-related cell damage, hypoxia, ischemia, and infections can result in extensive release of DAMPs. As many patients at the intensive care unit suffer from immune system-related complications, DAMPs could serve as markers for the prognosis of these patients and represent possible therapeutic targets. In the present review, we provide an overview of several well known DAMPs (high-mobility group box 1, heat-shock proteins, s100 proteins, nucleic acids, and hyaluronan) and their effects on the immune system. Furthermore, we discuss the role of DAMPs as markers or therapeutic targets in several conditions frequently encountered in critically ill patients, such as sepsis, trauma, ventilator-induced lung injury, and cardiac arrest.